On the retirement effect of inheritance: Heterogeneity and the role of risk aversion - Bertrand Garbinti; Simon Georges-Kot (European Central Bank (ECB), 2019)
This paper provides new insights on the effect of inheritance receipt on retirement. We build on lifelong information on inheritances received and labor market transitions available for respondents of the French Wealth Survey. This feature allows us to compare current retirement rates among current and future inheritors. Chances of current retirement are 40% higher among current inheritors than among individuals who will inherit in the next two years, but there is substantial heterogeneity in this effect across socio-demographic groups. The effect is also stronger for individuals with a higher risk aversion, which we interpret with a simple theoretical model.
Keywords: J14; J26; 330; Retirement; inheritance; labor supply; risk aversion